Is systemic inflammatory response index (SIRI) a reliable tool for prognosis of gastric cancer patients without neoadjuvant therapy - YEGEN, ŞEVKET CUMHUR (My University, 2023)
Background: The systemic inflammatory response index (SIRI), which depends on peripheral neutrophil, monocyte, and lymphocyte count, was found as an effective prognostic indicator for various malignancies. This study aims to investigate the predictive value of preoperative SIRI in the prognosis of gastric cancer patients without neoadjuvant therapy. Methods: The patients who underwent gastric cancer surgery in Marmara University Hospital\"s General Surgery Department between 2019 and 2021 were analyzed retrospectively. SIRI was calculated from preoperative peripheral blood samples\" neutrophil, lymphocyte, and monocyte count. The optimal cut-off value for SIRI was calculated by the receiver operating characteristics (ROC) curve and was found to be 1.35. The clinicopathological outcomes and overall survival (OS) were analyzed under two groups according to the SIRI values lower or higher than 1.35. Results: The number of eligible patients was 199. The median follow-up time was 25 (1-56) months. The higher SIRI was associated with male gender (p = 0.044), lower serum albumin (0.002) level, and Clavien-Dindo (CD) Grade III and higher complications (p = 0.018). However, there was no significant difference between the groups regarded pathological tumor, nodes, and metastases (TNM) stages, histological grade, and Lauren Type. In addition, OS and stage-specific OS were similar between the groups. Conclusions: SIRI may be a valuable and effective predictive indicator for postoperative morbidity. The prognostic performance of SIRI on long-term OS is still controversial. Further investigations are needed into this topic.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; systemic inflammation response index; neoadjuvant chemoradiotherapy; survival; overall; gastric cancer; COMPLICATIONS; CHEMOTHERAPY; SURVIVAL; RATIO; systemic inflammation response index; neoadjuvant chemoradiotherapy; survival; overall; gastric cancer